A new species of terrestrial planarian of the genus Microplana (Platyhelminthes: Turbellaria; Tricladida: Continenticola) from Yorkshire, United Kingdom; with a discussion of Microplana humicola Vejdovsky 1890 - Jones, Hugh D.; Mcdonald, Jillian C. (Zootaxa, 2021)
Two mostly white terrestrial planarians, about 7 mm long, found in a garden in Yorkshire, UK, are described. They have a single pair of eyes and both specimens are fully mature, with a single pair of ovaries, several testes, a conical penis papilla and a genito-intestinal duct, characters of the genus Microplana, but differ in color and size from other species of the genus and are described as Microplana edwardsi sp. nov.